2004
DOI: 10.1021/ma048934l
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Properties of Poly(methyl methacrylate)s Containing Tethered and Untethered Polyhedral Oligomeric Silsesquioxanes

Abstract: Poly(methyl methacrylate)s (PMMA) containing both tethered and untethered polyhedral oligomeric silsesquioxanes (POSS) were examined through the use of wide-angle X-ray diffraction (WAXD), differential scanning calorimetry (DSC), and rheological characterization. The presence of tethered-POSS in entangled copolymers leads to a decrease in the plateau modulus (G N 0 ) when compared with PMMA homopolymer. Two untethered-POSS fillers, cyclohexyl-POSS and isobutyl-POSS, were blended with PMMA homopolymer. Both DSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
164
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 209 publications
(182 citation statements)
references
References 46 publications
16
164
2
Order By: Relevance
“…These fractional free volume values are plotted in Figure 9. The free volume data in Figure 9 help clarify our previous results for PMMA filled with crystallizable-POSS species [13]. This earlier study reported that the POSS had a strong tendency to phase-separate into crystallites, even at loadings of φ = 0.01, and we could not find a clear trend in free volume with increasing POSS content.…”
Section: Time-temperature Superposition and Free Volumesupporting
confidence: 76%
See 2 more Smart Citations
“…These fractional free volume values are plotted in Figure 9. The free volume data in Figure 9 help clarify our previous results for PMMA filled with crystallizable-POSS species [13]. This earlier study reported that the POSS had a strong tendency to phase-separate into crystallites, even at loadings of φ = 0.01, and we could not find a clear trend in free volume with increasing POSS content.…”
Section: Time-temperature Superposition and Free Volumesupporting
confidence: 76%
“…In both cases, the POSS filler tended to phase separate into microcrystallites, even at loadings as small as φ = 0.01. Despite this phase separation, we observed a slight decrease in the viscosity for loadings φ < 0.05 [13]. This decrease was attributed to a small amount of molecularly-dispersed POSS particles that plasticized the matrix in the melt state at small loadings; however we did not observe a decrease in either T g or an increase in the fractional free volume f 0 , which would be expected if plasticization were occurring.…”
Section: Introductioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In our initial study of POSS-poly(methyl methacrylate)(PMMA) blends (Kopesky et al 2004), we incorporated two monodisperse, crystallizable T 8 POSS components into PMMA: cyclohexyl-POSS and isobutyl-POSS. Each was blended separately with PMMA and we observed a strong thermodynamic driving force toward phase separation of the POSS into crystallites with observed diameters in the range 50 nm ≤ d ≤ 5 µm.…”
Section: Previous Workmentioning
confidence: 99%
“…Thus, POSS nanoparticles can be dispersed at a molecular level (1-3 nm) [4] and, because of their synthetically well-controlled functionalization, can be incorporated into polymers by different polymerization techniques with minimal processing disruption. [5][6][7] This excellent dispersion at the molecular scale prevents phase separation and assures the macroscopic homogeneity of the materials. [8] In this way, new optical hybrid materials based on POSS nanoparticles as the inorganic part overcome some of the most important limitations intrinsic to sol-gel hybrid composites while maintaining the physical, chemical, and mechanical combined advantages of organic-inorganic systems.…”
mentioning
confidence: 99%